The Integration of Remote Sensing Data for Lineament Mapping in the Semanggol Formation, Northwest Peninsular Malaysia - Azman, A.I. (Institute of Physics Publishing, 2020)
The objec tive of this study is to prepare a final lineament map of three parts of the Semanggol Formation and its adjacent areas, located in northern Peninsular Malaysia. Landsat 5 TM, Landsat 7 ETM+, Landsat 8 OLI, digital elevation model (DEM) and drainage pattern were used to trace lineament. These data were digitally processed to enhance the visibility of data and derive to twenty-four images. Only negative lineaments with length more than 2 km were traced by using manual lineament extraction method. Based on the results, there are differences in the number of lineaments and total length in each data, caused the lineaments to have to compare each other. The lineaments identified from all data were integrated and evaluated to produce a final lineament map. A total of 645 lineaments were identified with a total length of 2264.42 km and a maximum length of 26.84 km. The trend of the lineaments was correlated with faults in the published geological map, especially in the Bok Bak Fault. This method proved that lineaments could be traced more accurately with the utilisation of various remote sensing data. Â© Published under licence by IOP Publishing Ltd.